The Effect of Macro-Micro Nutrient Fertilizers and Plant Spacing on the Growth (Brassica juncea L.) - Herlangga, Ardy Putra; Ikhwan, Ali; Muhidin (Universitas Muhammadiyah Malang, 2024)
Brassica juncea L. is a much-loved vegetable species in Indonesia. To improve the quality and quantity of mustard plants, agricultural intensification efforts are needed through macro-micro fertilisers that maintain the balance of soil nutrients. This study aims to determine the response of mustard plants to the application of macro-micro fertilisers. The research was conducted in Claket Village, Pacet District, Mojokerto Regency at an altitude of 470 masl with a daily temperature of 21-30°C. The method used was a factorial Randomised Group Design (RAK) with two factors (fertiliser dose and spacing) and three replications. Variables observed included increase in plant height, number of leaves, wet weight, dry weight, and water content. Data analysis used F test and BNJ 5%. The results showed that the interaction of macro-micro fertiliser dose and planting distance gave a significant effect on all variables, except dry weight due to high water content in mustard greens.